The Spatial Know-How of Graffiti - Jannes van Loon (lo Squaderno, 2016)
My research interest lies in understand the spatial behaviour of graffiti writers (van Loon, 2014). Although graffiti writers have unique perspectives on urban landscapes that determine where and what type of graffiti they produce, they also have collective or shared senses of place – i.e., a spatial know-how that structures their production (Castree, 2003).